You can subtitute a=1, b=1, or c=1

Algebra Level pending

Given that a a , b b , and c c are roots from the equation x 3 2017 x 2 + 2017 x 1 = 0 \large \color{#D61F06}{x^{3}}-\color{#EC7300}{2017x^{2}}+\color{#CEBB00}{2017x}-\color{#20A900}{1}=\color{#333333}{0} Find the value of a b + b + 1 c a + a + 1 + c a + a + 1 b c + c + 1 + b c + c + 1 a b + b + 1 \large \color{#3D99F6}{\frac{ab+b+1}{ca+a+1}}+\color{#69047E}{\frac{ca+a+1}{bc+c+1}}+\color{magenta}{\frac{bc+c+1}{ab+b+1}}


The answer is 2017.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Relevant wiki: Vieta's Formula Problem Solving - Basic

χ = a b + b + 1 c a + a + 1 + c a + a + 1 b c + c + 1 + b c + c + 1 a b + b + 1 Vieta’s formula: a b c = 1 = a b + b + a b c c a + a + 1 + c a + a + a b c b c + c + 1 + b c + c + a b c a b + b + 1 = b ( a + 1 + c a ) c a + a + 1 + a ( c + 1 + b c ) b c + c + 1 + c ( b + 1 + a b ) a b + b + 1 = b + a + c Vieta’s formula: a + b + c = 2017 = 2017 \begin{aligned} \chi & = \frac {ab+b+{\color{#3D99F6}1}}{ca+a+1} + \frac {ca+a+{\color{#3D99F6}1}}{bc+c+1} + \frac {bc+c+{\color{#3D99F6}1}}{ab+b+1} & \small \color{#3D99F6} \text{Vieta's formula: }abc = 1 \\ & = \frac {ab+b+{\color{#3D99F6}abc}}{ca+a+1} + \frac {ca+a+{\color{#3D99F6}abc}}{bc+c+1} + \frac {bc+c+{\color{#3D99F6}abc}}{ab+b+1} \\ & = \frac {b\cancel{(a+1+ca)}}{\cancel{ca+a+1}} + \frac {a\cancel{(c+1+bc)}}{\cancel{bc+c+1}} + \frac {c\cancel{(b+1+ab)}}{\cancel{ab+b+1}} \\ & = \color{#3D99F6}b + a + c & \small \color{#3D99F6} \text{Vieta's formula: }a+b+c = 2017 \\ & = \boxed{\color{#3D99F6}2017} \end{aligned}

Skye Rzym
Apr 7, 2017

From Vieta's Theorem, we get a + b + c = 2017 a+b+c=2017 and a b c = 1 abc = 1 And then, let a = p q a=\frac{p}{q} , b = q r b=\frac{q}{r} , and c = r p c=\frac{r}{p} . Starting from a b + b + 1 c a + a + 1 + c a + a + 1 b c + c + 1 + b c + c + 1 a b + b + 1 \frac{ab+b+1}{ca+a+1}+\frac{ca+a+1}{bc+c+1}+\frac{bc+c+1}{ab+b+1} = p q . q r + q r + 1 r p . p q + p q + 1 + r p . p q + p q + 1 q r . r p + r p + 1 + q r . r p + r p + 1 p q . q r + q r + 1 =\frac{\frac{p}{q}.\frac{q}{r}+\frac{q}{r}+1}{\frac{r}{p}.\frac{p}{q}+\frac{p}{q}+1}+\frac{\frac{r}{p}.\frac{p}{q}+\frac{p}{q}+1}{\frac{q}{r}.\frac{r}{p}+\frac{r}{p}+1}+\frac{\frac{q}{r}.\frac{r}{p}+\frac{r}{p}+1}{\frac{p}{q}.\frac{q}{r}+\frac{q}{r}+1} = p r + q r + 1 r q + p q + 1 + r q + p q + 1 q p + r p + 1 + q p + r p + 1 p r + q r + 1 =\frac{\frac{p}{r}+\frac{q}{r}+1}{\frac{r}{q}+\frac{p}{q}+1}+\frac{\frac{r}{q}+\frac{p}{q}+1}{\frac{q}{p}+\frac{r}{p}+1}+\frac{\frac{q}{p}+\frac{r}{p}+1}{\frac{p}{r}+\frac{q}{r}+1} = p + q + r r p + q + r q + p + q + r q p + q + r p + p + q + r p p + q + r r =\frac{\frac{p+q+r}{r}}{\frac{p+q+r}{q}}+\frac{\frac{p+q+r}{q}}{\frac{p+q+r}{p}}+\frac{\frac{p+q+r}{p}}{\frac{p+q+r}{r}} = q r + p q + r p =\frac{q}{r}+\frac{p}{q}+\frac{r}{p} = a + b + c =a+b+c = 2017 =\boxed{2017}

That's a good substitution to use when a b c = 1 abc = 1 .

Calvin Lin Staff - 4 years, 2 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...